PHYTOSYNTHESIS OF CADMIUM OXIDES NANOPARTICLES BY CRUDE EXTRACT OF URTICA DIOICA - ABDULHADI, BARAA H.; GALILL, RAGHAD DH. ABDUL; ABD, AHMED N. (Journal of Duhok University, 2023)
This study was identifying the flavonoids in Urtica dioica and using this extract to phytosynthesis of Cadmium oxides nanoparticles: CdO, CdO2 with characterization about them. The results obtained from the HPLC analysis found nine compounds, which included: Rutin 26.14 % was most abundant, followed by Chlorogenic acid 22.2 %, Naringin, Meyrecetin, Quercetin, Kaempferol, Vanallic acid, Ellagic acid and Isorhamantin. Two procedures were used to phytosynthesis NPs. The results showed that their average size (calculated by AFM) were: (75.25 and 70.34) nm for procedure1and procedure 2, respectively. From SEM study, there were nanorods particles produced by procedure 1 with dimensions range less than 50 nm, in addition, to nano plate with one diminution lower than 50 nm. While in procedure 2, the particles were spherical nanoparticles crystals with nanorods their sizes were (˂ 25) nm. The same features were seen in TEM images. The FTIR results showed strong bands are observed at (524.6 and 501.5) cm-1 for procedure 1 and 2, respectively, which attributed to Cd-O stretching vibrations. The XRD patterns of each procedure produce a mixture of nanoparticles: CdO and CdO2. The average crystallite size of NPs was: (14.74 and 13.97) nm for procedure 1 respectively, and (16.8 and 13.9) nm, respectively. From UV visible spectral, the absorption spectra exhibit strong absorption at 290 nm and 300 nm for procedures (1 and 2), respectively. Their energy band gaps were: (3 and 4.4) eV, respectively